Designing A Computer Network Monitoring System With Sms Notifications Using The Dude - Riki Irawansyah; Khairil Khairil; Rizka Tri Alinse (Penerbit Jurnal Indonesia, 2023)
One system that can perform network monitoring with SMS notifications is using The Dude. This network monitoring system with SMS Notification aims to make network admins aware of network conditions wherever they are. In monitoring the network the dude can do based on the ip address entered, the dude is open source, which is one of the software or tools built into Mikrotik, in the process of installing the dude does not require large storage space. In monitoring the network the dude will display a green indicator, which is on and red, which is off, to monitor the network the dude does it based on the IP Address per each device connected to the network. The Dude can perform network monitoring on the SMA N 6 Bengkulu Selatan computer network in the form of notification of devices on or off. The results of the monitoring will be sent in the form of notifications to the admin cellphone in the form of SMS, in sending SMS notifications, the dude takes +/- 2 minutes, the time for sending SMS notifications is calculated based on the condition of the device on or off until the notification is received or received on the cellphone.